ANALYSIS AND DEVELOPMENT OF A REAL-TIME RESELLER INFORMATION SYSTEM BASED ON MOBILE KOTLIN TECHNOLOGY AT PT. SCUTO INDONESIA - Wisnu Sukma Maulana (Asosiasi Dosen Muda Indonesia, 2022)
Scuto Indonesia (Scuto) has a reseller whose job is to offer automotive maintenance services to prospective customers who are outside of Scuto outlets. Problems arise when the resellers spread throughout Indonesia have to wait a long time from the data that is sent manually to the center via email. Thus, Scuto does not yet have a system to facilitate the process from resellers offering potential customers to claim bonuses from the sales that have been made by resellers in real-time. A technology approach that is suitable for real-time data problems with regard to operational aspects, then what is used is a mobile-based technology. In addition to these problems, the next problem is making the desired system must be in accordance with a budget that is quite efficient. Because, Scuto itself is a company that is still developing and does not have the resources or budget that is large enough to fund large system-making projects. One solution is to use the latest mobile technology, Kotlin. Kotlin technology can be run on two versions, namely mobile (Android and iOS) and also the web version with only one programming. Thus, the use of Kotlin technology can save the resources of a team of programmers who previously needed many different teams simultaneously, namely Android programmers, iOS programmers, and web programmers, now only become one team of programmers.